Mutational Characterization of Cutaneous Melanoma Supports Divergent Pathways Model for Melanoma Development - Millán-Esteban, David; Peña-Chilet, María; García-Casado, Zaida; Manrique-Silva, Esperanza; Requena, Celia; Bañuls, José; López-Guerrero, Jose Antonio; Rodríguez-Hernández, Aranzazu; Traves, Víctor; Dopazo, Joaquín; Virós, Amaya; Kumar, Rajiv; et al. (Cancers, 2021)
According to the divergent pathway model, cutaneous melanoma comprises a nevogenic group with a propensity to melanocyte proliferation and another one associated with cumulative solar damage (CSD). While characterized clinically and epidemiologically, the differences in the molecular profiles between the groups have remained primarily uninvestigated. This study has used a custom gene panel and bioinformatics tools to investigate the potential molecular differences in a thoroughly characterized cohort of 119 melanoma patients belonging to nevogenic and CSD groups. We found that the nevogenic melanomas had a restricted set of mutations, with the prominently mutated gene being BRAF. The CSD melanomas, in contrast, showed mutations in a diverse group of genes that included NF1, ROS1, GNA11, and RAC1. We thus provide evidence that nevogenic and CSD melanomas constitute different biological entities and highlight the need to explore new targeted therapies.
Keywords: melanoma; etiopathogeny; mutations